Extent of Recidivism among Juvenile Delinquents and Their Later Careers (Archives of Criminology, 1974)
The subject of this work are the findings of studies of the follow-up period intended to establish the further fate of 343 juvenile delinquents aged 10-16, who had been guilty of theft while still under 17.In 1961 detailed, criminological research was initiated in the Juvenile Court of Praga – one of the districts of Warsaw – (records were studied, interviews undertaken in the environs, homes and schools were conducted), which embraced all the 180 juvenile delinquents between 10-16 years, living in that district, who during the course of one year had been found guilty of theft. Further a study was made of the criminal records of 178 juvenile thieves from two other districts of Warsaw, all the juvenile delinquents who had been tried for theft by courts during the period from August 1961 to May 1962 being investigated in turn. In this way was obtained a total of 358 juvenile delinquents who had been found guilty of thefts. The idea was to find out how many of them were recidivists in the follow-up period. 33% of these juvenile delinquents were under 13 and 67% were between 13 and 16 years. The division into these two groups was justified because of the different approach of the Polish penal code to minors up to the age of 13: as regards such juvenile delinquents, the court may apply educational measures only: reprimand, supervision by parents, probation and placing in an educational institution. As regards delinquents between 14 and 16, the court may also apply correctional measures – i.e. approved schools.In the present work, the author accepts as basic criterion for defining the recidivist the fact that he has faced in a Juvenile Court a new charge of theft. The category of those not considered as recidivists includes only delinquents charged once with theft. Each juvenile delinquent who has been charged (usually by the police) a second or third time with theft already figures as a recidivist with 2, 3, 4 and more appearances in court. Moreover, it was possible during the investigations, combined with detailed interviews in the homes of the delinquents, additionally to qualify as recidivists such juvenile delinquents shown to have stolen though not brought before a court.Taking into account the variety of criteria applied to recidivists, they have been divided into the following categories:(a) first of all, formal criteria were applied: considered as recidivists were those concerning whom the court had previously applied educational and correctional measures. Here, the percentage of recidivists amounted to 37.7;(b) this percentage increased to 48.6 when considered as recidivists were all those who had been charged at least twice with theft, including those concerning whom the court had not considered it relevant to apply any new measures;(c) this percentage was still higher (61.2), when listed as recidivists were all those whom the court had found guilty of at least two thefts;(d) interviews in the environment conducted as regards 180 juvenile delinquents in a single district revealed in addition that these data too were not entirely reliable in defining recidivists. Data from interviews showed that the percentage of delinquents who had committed more than one theft amounted to as much as 78.5.It was also found that, when applying the first, formal criterion recidivists among the older delinquents (46%) were far greater in numbers than among the younger (20%). The second criterion – at least two thefts – showed that the difference between older and younger delinquents as regards the percentage of recidivism among them (82.2% 73.2%) was only slight.These data indicate that the formal criterion for recidivism, used by Juvenile Courts, does not reflect the actual extent of this phenomenon. This is the more important since, the latter, broader definition, was found to be the most satisfactory for prognostic purposes. It was established that during the two-year follow-up period a substantially larger number of juvenile delinquents previously listed, according to the first formal definition, as not being recidivists (47%), faced charges than was the case with those listed according to the second definition (17.6%).Criminological investigations – combined with interviews conducted in their families – of 180 juvenile delinquents from a single district, revealed that juvenile delinquents charged with theft are as a rule socially maladjusted children, showing the first symptoms of social maladjustment even in the first grades of primary school. With 62% symptoms of demoralization were recorded with children between 7 and 10 years of age. A typical phenomenon with these juveniles is a considerable lag in their school studies, found as regards 95% of older and 76% of younger juveniles. A lag of at least two years was found with 77% of the older and 37% of the younger individuals investigated. The majority of these systematically played truant; 37% of the younger and 70% of the older juveniles had run away from home. Only as regards 33% was it not found that they consumed alcohol; 26% drank at least once a week; 25% of the recidivists were heavy drinkers.On the basis of data obtained from mothers during interviews (and for 50% of the cases also from child guidance clinics, institutions etc.) it was possible with 60% of the older investigated delinquents to establish various types of personality disorders; 26% were suspected of having suffered organic disturbances of the central nervous system; data indicating such diseases in the past were more frequently found with recidivists (37%) than with those who were not recidivists (13%).Those investigated were for the most part brought up in an unsatisfactory family environment. It was found that in 46% of the families fathers or step-fathers systematically drank alcohol to excess; delinquency of fathers was noted in 31% of the families, and in 9% the mothers were suspected of prostitution. As many as 67% of the brothers revealed symptoms of demoralization and 47% had committed theft.Recidivists differed markedly from non-recidivists as regards such negative features, characterizing the family environment as: systematic abuse of alcohol, unhappy married life of the parents, children very poorly cared for.Of all the 358 thieves investigated, a mere one-third were as juveniles (under 17) charged only once: thus they were not recidivists according to the criteria accepted in the investigation; 21% had twice faced a court; 11% – three and 34% – four or more times had been charged before a Juvenile Court.The differentiated groups of the youngest and oldest among those we investigated did not differ markedly as regards the number of appearances in court while under age.Consideration was next given to further delinquency during the period when the investigated were young adults i.e., when they were between 17 and 20. New offences were noted during that period with 50% of the former defendants who, previously had been juveniles. It also emerged that the number of charges preferred while they were under age was of essential significance for recidivism during the period when those investigated were already young adults. Among those who had been charged only once as juveniles, only 27% were afterwards convicted between the age of 17 and 20; among those charged twice – 48%; beginning with 3 charges, the percentage of later recidivists amounted to 65.8, and with 4 and more charges – to as much as 78.7%.The number of convictions while juveniles indicates a correlation not only with the actual fact of recidivism when those concerned were still young adults, but also the intensification of recidivism between 17 and 20. The majority of those who while juveniles had only one case against them, were subsequently convicted only once. But of those who while juveniles were charged at least three times, the majority (64%) had multiple convictions between 17 and 20.Typical of offences committed by those who had been charged with theft as juveniles, continued to be theft; close on half of those investigated, however – and this should be emphasized – were convicted for offences against the person, officials or the authorities, and these as a rule were offences committed while intoxicated.One-third of the subjects spent in prison at least half of the four-year period, while they were young adults.In 1972, when the last follow-up period was studied, ten years had elapsed since the beginning of the investigation of the delinquents who had committed theft while juveniles. The younger among them were at that time 20 to 23 years old; the older – 24 to 27 (the average age being about 26 years). As regards these 243 older investigated individuals, it was possible to examine not only the period when they were young adults, but also the later period, after they were already 21 years old; this later period was in their case sufficiently to make it possible properly to evaluate whether during that time they had ceased committing offences or whether they continued to do so.Further delinquency of the older among those investigated during the period after 17 until their average age was about 26, was as follows:– It emerged that only 38% had not been convicted at all after the age of 17. The overwhelming majority of them (83%) had been charged only once or twice while under age.– 17% had been convicted only between 17 and 20, while 13% had been convicted only after 21.– 32% were convicted as young adults as weil as later after the age of 21. In this group, the majority (73%) had been charged before a court at least three times as juveniles.As regards the older among those investigated for the entire follow-up period, it was confirmed that the majority showed a correlation with what happened during their juvenility: further delinquency as well as persistent recidivism was found more frequently with those who were more frequently charged as juveniles.During the entire follow-up period, 19% of the older individuals were convicted only once, l3% – twice, and 30% – at least three times. The category with multiple convictions, recidivists convicted at least four times amounted to 20%, which certainly is a substantial figure, having regard to the relatively long prison sentences passed on those convicted two and three times.It should be added that though interviews in the environment during the follow-up period were lacking, making impossible a proper evaluation of the social adjustment of those investigated who during that period had no new convictions or were convicted only once, the data obtained enable the drawing of conclusions which are important for social policy. Note that even frorn among the investigated juveniles who were charged only once before a court, as many as 42% were later convicted after 17; this points to the necessity of a thorough examination of even apparently minor cases of theft involving those under age who previously had not been convicted. The extent of persistent recidivism revealed demonstrates the poor effectiveness of methods used as far in dealing with juvenile delinquents who revealed symptoms of marked social maladjustment.